Comparative efficacy of different insecticides, biopesticides and plant extracts against the cutworms - Sharma , S D; Sidhu, Kawartej Singh (Indian Journal of Plant Protection, 2023)
A field experiment was conducted at Hill Agricultural Research and Extension Centre, Bajaura (1100 m a.m.s.l.), Kullu, Himachal Pradesh during Kharif season of 2018 on maize crop (variety Girija) to evaluate different insecticides, biopesticides and plant extracts against the cutworms infesting maize crop. The results revealed that the seedling mortality by cutworms in different treatments varied from 0.00 to 9.91 per cent as compared to control with 17.40 per cent. Treatment consisting of seed treatment with imidacloprid (6 ml/kg) followed by foliar spray of chlorpyriphos (2.0 ml/L) was the most effective treatment giving the best safety to the crop and resulting in no seedling mortality. There was 100 per cent reduction in the cutworm population over control in this treatment with the highest grain yield (57.26 q/ha). This treatment was followed by a treatment (T3) consisting of seed treatment with thiomethoxam 7 g/kg of seed resulting in 1.89 seedling mortality and thus recording 89.13 per cent reduction in the cutworm population over control with grain yield of 55.05 q/ha. The cost benefit ratio was highest in case of treatment T1 (seed treatment with imidacloprid) with the net monetary returns of Rs. 70788/ha.